2009
DOI: 10.2960/j.v42.m648
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Stomach contents analysis showed that the three whale species are highly dependent on small pelagic fish, i.e. Japanese anchovy, Pacific saury and mackerels in addition to copepods and euphausiids. Pianka's niche overlap index showed high diet overlap among whale species that occur in some areas where they feed on pelagic fish. Canonical correspondence analysis (CCA) indicated environmental and biological factors significantly contribute to the diet composition of whales. CCA also explained the distribution pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In this sense, sei whale have been reported to feed on a variety of prey species. In the Northern Hemisphere, food species include copepods, euphausiids, amphipods, decapods, cephalopods, and fish (Nemoto, 1959(Nemoto, , 1962Kawamura, 1973;Konishi et al, 2009). Even though the prey species are highly dependent on an ocean basin, swarming characteristics of the prey, availability, and seasonal conditions (Rice, 1977;Budylenko, 1978;Horwood, 1987;Flinn et al, 2002;Konishi et al, 2009), sei whales demonstrate a preference for zooplankton (Kawamura, 1973;Watkins & Schevill, 1979).…”
Section: Photo-identified Whalesmentioning
confidence: 99%
“…In this sense, sei whale have been reported to feed on a variety of prey species. In the Northern Hemisphere, food species include copepods, euphausiids, amphipods, decapods, cephalopods, and fish (Nemoto, 1959(Nemoto, , 1962Kawamura, 1973;Konishi et al, 2009). Even though the prey species are highly dependent on an ocean basin, swarming characteristics of the prey, availability, and seasonal conditions (Rice, 1977;Budylenko, 1978;Horwood, 1987;Flinn et al, 2002;Konishi et al, 2009), sei whales demonstrate a preference for zooplankton (Kawamura, 1973;Watkins & Schevill, 1979).…”
Section: Photo-identified Whalesmentioning
confidence: 99%
“…In contrast, common minke whales are opportunistic D r a f t 27 feeders known to feed on a variety of prey species. They feed on schooling small pelagic fishes such as the Japanese anchovy (Engraulis japonicus Temminck and Schlegel, 1846), Pacific saury (Cololabis saira Brevoort, 1856), and krill in the western North Pacific (Tamura and Fujise 2002;Murase et al 2007;Konishi et al 2009). Notably, krill fed on by common minke whales in the western North Pacific is smaller than Antarctic krill in terms of body size.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown species-specific growth patterns, such as an increase in the length of the head region associated with a decrease in the length of the tail region in blue and fin whales [15] but no obvious trend in sei whales [16]. The prey species of Balaenoptera species range from planktonic crustaceans (copepods and krill) to schooling fishes, depending on the species [18] [19] [20] [21]. They feed using a unique system called "lung feeding" in which they engulf a large mass of water with prey and extrude only the water by filtering the prey items using their baleen plates [22].…”
Section: Introductionmentioning
confidence: 99%